2004
DOI: 10.1182/blood-2003-09-3058
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin cooperates with FLT3-ligand in the generation of plasmacytoid dendritic cell precursors from human hematopoietic progenitors

Abstract: IntroductionDendritic cells (DCs) are professional antigen-presenting cells (APCs) that display an extraordinary capacity to stimulate naive T cells and to initiate primary immune responses. 1 Recent studies suggest that DCs also play critical roles in the induction of peripheral immunologic tolerance, regulate the types of T-cell immune responses, and function as effector cells in innate immunity against microbes. 2,3 The diverse functions of DCs in immune regulation depend on the functional plasticity of DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 29 publications
6
90
0
Order By: Relevance
“…Purified CD34 1 HSCs were cultured in vitro with Flt3L and TPO for 14, 21 and 28 days. In agreement with Chen et al, 26 21 days was optimal for the expansion and development of all DC subsets identified 26 and this time point was thus used in all subsequent experiments (data not shown). At day 21, five major populations of cells could be distinguished: CD14 1 monocytes, CD14 2 HLA-DR 1 CD11c 1 CD1b/c 1 and CD14 2 HLA-DR 1 CD11c int CLEC9A 1 cDC, HLA-DR int CD11c 2 CD123 1 pDC and HLA-DR 2 CD11c 2 CD123 2 CD1b/c 2 CLEC9A 2 cells (subsequently referred to as DC marker-negative cells) (Figure 1b and d).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Purified CD34 1 HSCs were cultured in vitro with Flt3L and TPO for 14, 21 and 28 days. In agreement with Chen et al, 26 21 days was optimal for the expansion and development of all DC subsets identified 26 and this time point was thus used in all subsequent experiments (data not shown). At day 21, five major populations of cells could be distinguished: CD14 1 monocytes, CD14 2 HLA-DR 1 CD11c 1 CD1b/c 1 and CD14 2 HLA-DR 1 CD11c int CLEC9A 1 cDC, HLA-DR int CD11c 2 CD123 1 pDC and HLA-DR 2 CD11c 2 CD123 2 CD1b/c 2 CLEC9A 2 cells (subsequently referred to as DC marker-negative cells) (Figure 1b and d).…”
Section: Resultssupporting
confidence: 82%
“…[48][49][50][51][52] We now show that in addition to pDCs, 26 this culture system also supports the development of both the CD1b/c 1 and CLEC9A 1 DCs and CD14 1 monocytes. This is in keeping with observations that humans injected with Flt3L show an increase in both DCs and monocytes.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations